DegU and YczE Positively Regulate the Synthesis of Bacillomycin D by Bacillus amyloliquefaciens Strain FZB42 - Koumoutsi, Alexandra (American Society for Microbiology (ASM), 2007)
Environmental strain Bacillus amyloliquefaciens FZB42 differs from the domesticated model organism of the same genus, Bacillus subtilis 168, in its ability to promote plant growth and suppress plant-pathogenic organisms present in the rhizosphere. This behavior is exerted mainly through the production of several nonribosomal cyclic lipopeptides and polyketides, which exhibit a broad range of action against phytopathogenic bacteria, fungi, and nematodes. Here, we provide evidence that the synthesis of the main antifungal agent of B. amyloliquefaciens FZB42, bacillomycin D, is regulated in multiple layers. Expression of the bacillomycin D operon (bmy) is dependent on a single σ(A)-dependent promoter, P(bmy) and is favored in its natural host by the small regulatory protein DegQ. The global regulators DegU and ComA are required for the full transcriptional activation of bmy. DegU retains a key role since it binds directly to two sites located upstream of the bacillomycin D promoter. Moreover, both DegU and a transmembrane protein of unknown function, YczE, act on a later level of gene expression, exerting their posttranscriptional effects in a hitherto-unknown manner.